Pengembangan Buku Ajar Kalkulus 1 untuk Meningkatkan Kemampuan Pemahaman Konsep Kalkulus 1 pada Tahap Preliminary Research - Dewi Devita; Syelfia Dewimarni; Deby Erdriani (Departement of Mathematics Education, 2023)
Learning, which has been carried out online for the past 2 years due to Covid-19, has made the learning outcomes of calculus 1 students of the industrial engineering study program at Putra Indonesia University YPTK Padang not good. Currently, the Covid-19 chart is sloping. Learning on campus is back to face-to-face and blended learning. For this reason, researchers conducted research on the development of calculus 1 textbooks to increase understanding of the concept of calculus 1 for students of the industrial engineering study program at Putra Indonesia University YPTK Padang. The purpose of this research is for students to learn optimally so they can improve their understanding of calculus 1 concepts. This type of research is Research and development research in accordance with the development procedure proposed by Plomp, namely Preliminary research, Prototyping stage and Assessment phase. This study describes the Preliminary research stage, which is the initial stage of research on developing a calculus 1 textbook. The calculus 1 textbook developed in this study is expected to be a source of reference for the main study of calculus 1 courses by students of the industrial engineering study program at Putra Indonesia University YPTK Padang.